The Influence of Financial Performance and Environmental, Social, Governance (ESG) Score on Stock Return - Gabriella Angeline Darwanto; Yusni Warastuti (Jurnal Akuntansi, 2025)
This research aims to thoroughly examine the influence of financial performance and Environmental, Social, Governance (ESG) score on stock return. The study analyze how these financial and non-financial factors influence stock price movements and investor decision-making. This research sample consists of 47 companies from financial industry especially the banking subsector that are listed on the Indonesia Stock Exchange (IDX) during the period between 2020 and 2023. To analyze the relationships between the variables under study, multiple linear regression is employed as the primary analysis technique for the data, allowing for the systematic evaluation of the influence of financial performance and other relevant factors on stock returns, as well as the testing of the proposed research hypotheses. The result reveal that the solvability ratio, as indicated by CAR, the activity ratio measured by TATO, and ESG score have a significant positive impact on stock return. Meanwhile, liquidity ratio, represented by LDR and profitability ratio, measured by ROE, has no impact on stock return.